KEDUDUKAN HUKUM ADAT DALAM PENGUATAN PELESTARIAN NILAI-NILAI ADAT DALAM YURISPRUDENSI - Ali Aridi; Yana Sukma Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
The purpose of this research is to find out how the position of customary law is in the current national legal system and how to strengthen the preservation of customary values ​​in jurisprudence. Through research on normative law it was concluded that customary law is an unwritten rule that lives within the indigenous peoples of a region and will continue to exist as long as the community still fulfills the customary law that has been passed down to them from their ancestors before them. Therefore, the existence of customary law and its position in the national legal system cannot be denied even though customary law is unwritten and based on the principle of legality is an illegitimate law. Customary law will always exist and live in society. Customary law is a law that really lives in the awareness of the conscience of the community which is reflected in the patterns of their actions in accordance with their customs and socio-cultural patterns which are not contrary to national interests. The current era can indeed be called the era of the revival of indigenous peoples which is marked by the birth of various policies and decisions. However, what is equally important is the need for further study and development with its implications for drafting national laws and efforts to enforce applicable laws in Indonesia.